(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The presented scientific paper describes the optimization of the motion modes of a robot-manipulator with two translational and one rotational links in the plane of the manipulator rotation. Between the two extreme positions of the robot-manipulator grip, the trajectory of its movement was chosen, which is a straight line connecting these positions, since it is the shortest distance of a load moving. Along the selected trajectory during the entire movement cycle, the optimal movement modes were determined, where the average values of kinetic energy and energy of grip jerks with the load were used as optimization criteria. In the first case, a movement mode that provides a constant speed of a grid over the entire movement section was recieved. With this mode of movement, minimum energy consumption is ensured, but it cannot be used on the entire section of movement, because there are no start and stop sections in it. It is recommended to use the optimal energy mode in lines of steady movement. In the second case, a mode of movement in which the speed changes during the entire cycle of movement according to the curve of the fourth order, and the acceleration – of the third were obtained. Moreover, in contrast to the optimal energy movement mode, with the optimal jerk mode, the speed and acceleration of the grip at the beginning and at the end of the movement are equal to zero, so this mode can be used throughout the entire movement cycle. A complex mode of movement of the grip with a load was developed, where the optimal jerk mode of movement of the grip was used in separate sections of the start and stop, and in the section of steady motion – the optimal energy mode of movement. As a result of solving the inverse problems of kinematics, laws were established. They allow to determine optimal modes of motion of the grip in terms of the generalized coordinates of the robot-manipulator. It makes it possible to evaluate the characteristics of drive mechanisms and their control systems. A comparison of the kinematic characteristics of the grip in the optimal modes of movement with the determined characteristics of the generalized coordinates in the same modes of movement shows their fundamental difference. Optimal grip characteristics change smoothly, the generalized coordinates have a sign-changing character, which indicates the need for constant movement control by drive mechanisms. It was established that the design of the elements of the robot-manipulator has a significant influence on the nature of the change in the kinematic characteristics of the drive mechanisms along with the movement mode of the grip. As a result of the conducted research, the necessary parameters and characteristics of the drive mechanisms for the extension and rotation of the grip have been established for the implementation of its optimal modes of movement. It allows the development of their control system.